ESTIMATION OF COMBINING ABILITY INVOLVING QUALITY PROTEIN MAIZE (QPM) INBREDS UNDER TEMPERATE CONDITIONS - Z. A. DAR, A. A. LONE, B.A.ALAIE, GOWHAR ALI ASIMA GAZAL I. ABIDI, (The Bioscan, 2015)
Twenty-four quality protein maize (QPM) hybrids were generated by crossing eight QPM lines with three testers to estimate combining ability effects for yield and yield attributing traits. ANOVA for combing ability revealed significant mean squares of GCA and SCA for all the traits in individual and pooled analysis. Non additive gene action played a major role in expression of traits viz., plant height, number of kernel rows cob-1 and number of kernels row-1, 100-grain weight, grain yield plant-1 and protein content. Additive gene action also played a role in expression of traits like days to 50% silking, days to 50% tasseling and ear height. QPM line KDQPM-60 was identified as a good general combiner for grain yield plant-1 followed by KDQPM-21 and KDQPM-50. KDQPM- 60 was accompanied with significant and desirable GCA effects for other traits also. Crosses which exhibited highly significant and desirable SCA effects included KDQPM-14×VQL-1, KDQPM-60×VQL-17 and KDQPM- 21×VQL-2 for kernel rows cob-1 and KDQPM-50×VQL-1, KDQPM-60×VQL-17 and KDQPM-13×VQL-17 for grain yield plant-1. It can be concluded that the crosses having high SCA effects for grain yield plant-1and their parents with high GCA can be used directly as donors and exploited for future hybrid breeding programmes.